Neoplasms reproductive system: analysis of understanding and coping in men and women - Francisco Gilberto Fernandes Pereira; Marcia Barroso Camilo Ataide; Rebeca Barros da Silva; Juliana Faheina Moreira; José Osivan Mendonça Junior (Universidad de Alicante, 2017)
Objective: To analyze the understanding and coping strategies adopted by men and women against the disease of the reproductive system neoplasms. Methodology: A descriptive qualitative study involving 20 subjects hospitalized for chemotherapy. Information was collected through semi-structured interviews, which were organized and analyzed by the collective subject discourse analysis technique. Were followed by the ethics opinion 179/08. Results: by the speeches of the interviewees revealed three synthetic discourses, anchored on the following core ideas: masculinity and cancer; femininity and cancer; and adapt and overcome. To note that women demonstrated greater ability to adapt and overcome facing the diagnosis, while men perceive the disease as loss of virility and the essence of the man. Final thoughts: are divergent repercussions caused by cancers of the reproductive system in men and women, which causes different coping strategies and understanding of the disease.